SUFISTIC MORAL EDUCATION IN BUYA HAMKA'S THOUGHT: A LIBRARY-BASED THEMATIC ANALYSIS OF SPIRITUAL AND ETHICAL INTEGRATION - Asma'i Gunarsih; Akbar Yusgiantara; Baidi Baidi (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2025)
The crisis of values in modern education has created an urgent need for an Islamic education paradigm that is both intellectually focused and morally and spiritually transformational. This research seeks to thoroughly examine Buya Hamka's Islamic educational philosophy by highlighting the aspects of morality, spirituality, and nationality via a humanistic-transcendental lens. This study employs qualitative methods, including literature reviews and thematic analysis of primary texts such as Modern Sufism, Lembaga Budi, and Falsafah Hidup, to compile key conceptual categories: Sufi moral education, the integration of reason and revelation, humanist spirituality, and prophetic national education. The study's findings indicate that, according to Hamka, education is a blend of reason, spiritual ethics, and social responsibility aimed at cultivating an ideal human being. This study's contribution is the reinterpretation of Islamic educational philosophy that addresses the issues posed by Generation Z and the secularisation crisis in contemporary education. These results have significant implications for the reformulation of the Islamic education curriculum, the enhancement of teacher ability grounded on spiritual principles, and the development of a holistic educational paradigm in Indonesia and the broader Islamic world.